Performance analysis of generalized-k fading channels in vehicular communications - Aslan, Kardeş (My University, 2021)
Releasing autonomous vehicles in the near future; communication of vehicles with each other to circumvent traffic congestion, road safety, fuel-saving, efficient transportation, road tolls, their connecting over the internet and storing of data of vehicles on cloud and fog enforce research of vehicular communication systems. In the first chapter of this dissertation, non-wide sense stationary (WSS) vehicular channels having various issues are addressed. Then, the literature about vehicular channels are presented. Although shadowing effects are mostly neglected in the literature, it is known that it is available in the most wireless communication environment. Hence, a channel model like generalized-k (KG) including shadowing is a realistic one. Therefore, KG fading channels are described in the second chapter of this dissertation because the selected channel for each different topic addressed in this dissertation is the KG fading channel. In wireless communication, applying diversity techniques such as multiple-input-multiple-output (MIMO), maximum ratio combining (MRC), antenna selection, equal gain combining (EGC), beamforming is important in order to increase communication quality. One of them is the maximum ratio transmission (MRT) technique with low receiver complexity can make ultra reliable vehicular feasible in practice. In the third chapter of this dissertation, performance improvement with MRT over KG channels is investigated by considering error rates and outage probability (OP). In recent years, non-orthogonal multiple access (NOMA) has drawn a lot of attention due to serving multiple users in the same resource blocks (i.e., the same time-slots and frequency bands). It accomplishes that by multiplexing multiple users in the power domain with superposition coding (SC) at the transmitter and by using successive interference cancellation (SIC) at the receiver. Thus, it considerably reduces frequency scarcity and latency compared to orthogonal multiple access (OMA) techniques used in previous communication generations. Therefore, in the fourth chapter of this dissertation, the performance of downlink-non-orthogonal multiple access (NOMA) which provides a noticeable gain in the frequency spectrum, quite decreases latency, and is provisioned to be used in the fifth generation, is researched in KG vehicular fading channels. In the fifth chapter of this dissertation, the performance of uplink-NOMA over KG vehicular channels is studied. Frequency scarcity and latency leads inherently to a bigger problems in vehicular channels due to the requirement of fast and reliable. Therefore, NOMA is more important for vehicular channels than other channels. To this end, performance metrics such as OP, average channel capacity (AVC), and symbol error probability (SER) are mathematically analyzed for the considered system.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Vehicular channels; Generalized-k channels; Maximum ratio transmission; NOMA